PEEK composite insulating electromagnetic wire containing heat-conducting filler and preparation method thereof

CN122991728APending Publication Date: 2026-10-27ZHEJIANG CHENGFENG NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611457615.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]综上所述,现有技术面临的核心矛盾是:PEEK的耐高温性和机械强度优异,但其快速结晶特性导致与其他绝缘材料复合时层间互扩散不足;纳米填料的引入可提升绝缘性能,但多尺度颗粒的级配失调又导致涂层偏析和缺陷

Benefits of technology

通过将羟基化氮化硼纳米片引入纳米二氧化硅超支化聚酯体系并与聚醚醚酮复配,形成三层梯度复合绝缘结构,可利用羟基化氮化硼纳米片表面硼羟基与超支化聚酯末端羧基或羟基以及纳米二氧化硅表面硅羟基之间的氢键网络,抑制纳米填料团聚并改善界面相容性;通过不同片径羟基化氮化硼纳米片的级配组合,可利用沉降速率差异在涂层厚度方向形成自梯度分布,使大片径片层在底层富集形成导热阻隔骨架,小片径片层在上层富集形成界面锚定层;从而提升击穿电压、绝缘电阻、耐高温性能、层间剪切强度、局部放电起始电压和耐电晕性能,并改善填料分散均匀性和涂层结构稳定性。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a PEEK composite insulating electromagnetic wire containing a heat-conducting filler and a preparation method thereof, and relates to the technical field of insulating wires.The electromagnetic wire comprises a copper conductor and a first insulating layer, a second insulating layer and a third insulating layer arranged on the surface of the copper conductor in sequence; the first insulating layer and the third insulating layer are both composite layers of polyether ether ketone and nanosilica hyperbranched polyester; the second insulating layer is a nanosilica hyperbranched polyester layer containing hydroxylated boron nitride nanosheets; the total addition amount of the hydroxylated boron nitride nanosheets accounts for 2%-4% of the solid content of the nanosilica hyperbranched polyester, and the hydroxylated boron nitride nanosheets include hydroxylated boron nitride nanosheets with different flake diameters. During preparation, a mixed solution and a coating solution containing hydroxylated boron nitride nanosheets are prepared respectively, and the three-layer insulating structure is formed through sequential coating and baking. The application can improve the filler dispersibility and interfacial compatibility, form a gradient insulating structure, and improve the comprehensive insulating performance, high-temperature resistance and interlayer bonding performance of the electromagnetic wire.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of insulated wire technology, and in particular to a PEEK composite insulated electromagnetic wire containing thermally conductive filler and its preparation method. Background Technology

[0002] Polyetheretherketone (PEEK) is a high-performance thermoplastic engineering plastic with high heat resistance (stable operating temperature from -40°C to 260°C), excellent mechanical properties, and easy processing characteristics, making it a promising candidate for applications in electromagnetic wire insulation. With increasingly stringent requirements for electromagnetic wire insulation performance in high-end fields such as new energy vehicle drive motors, aerospace electrical systems, and high-frequency high-voltage power electronic equipment, PEEK-based insulation materials have attracted widespread attention. Currently, key performance indicators for electromagnetic wire insulation materials include breakdown voltage (BDV), partial discharge initiation voltage (PDIV), corona resistance, and oil aging resistance. Particularly in new energy vehicle motor applications, increasingly higher demands are being placed on the long-term reliability of PEEK electromagnetic wires under higher temperatures, higher voltages, and more severe operating conditions.

[0003] To address the performance limitations of PEEK alone, existing technologies attempt to combine it with other insulating materials, such as hyperbranched polyester. However, simply layering different materials easily leads to the formation of physical interfaces between the layers, resulting in space charge accumulation and localized electric field concentration at these interfaces, which can become the starting point for partial discharge. Existing insulated wires are prone to partial ionization discharge under high-frequency voltage impacts, and interface defects are one of the important causes of this phenomenon. Comparative data shows that when PEEK and hyperbranched polyester are simply combined as different insulating layers, the breakdown voltage is only about 1.5 kV, and the DC insulation resistance is only about 2 × 10⁻⁶. 10 Ω is orders of magnitude different from systems that truly form molecular-level complexes.

[0004] To further improve insulation performance, existing technologies attempt to introduce inorganic nanofillers such as nano-silica into polymer matrices. However, nanoparticles have large specific surface areas and high surface energies, making them prone to aggregation. Studies have shown that nano-SiO2 modified by hyperbranched surface grafting is less prone to aggregation in epoxy resin solutions. The introduction of long-chain free radicals can inhibit the aggregation of nano-SiO2, enhance the bonding strength between inorganic particles and epoxy groups, and introduce deep traps in the interfacial region, thereby significantly improving the dielectric properties of the composite material. However, the number of terminal groups in hyperbranched polyesters is limited, and they cannot completely cover all particle surfaces. Once agglomerates form, micropores and interfacial defects are formed after baking.

[0005] When particles of different sizes and densities coexist in a coating solution, their settling rates and Brownian motion intensities differ, easily leading to stratification, sedimentation, or localized enrichment. In insulating coatings, when the diameter of aggregated particles exceeds a certain range, the particles tend to settle in the liquid and cannot be uniformly dispersed. In actual production, this segregation results in uneven coating composition along the thickness direction, with excessive or insufficient fBNNSs in certain areas, dielectric constant gradient mismatch, and electric field concentration in filler-depleted regions, becoming the starting point for breakdown.

[0006] In summary, the core challenge of existing technologies is that while PEEK exhibits excellent high-temperature resistance and mechanical strength, its rapid crystallization characteristics lead to insufficient interlayer interdiffusion when composited with other insulating materials. The introduction of nanofillers can improve insulation performance, but the mismatch in multi-scale particle gradation results in coating segregation and defects. Current technologies fail to provide a solution that simultaneously addresses both insufficient interlayer interdiffusion and multi-scale particle gradation mismatch. Therefore, there is an urgent need to develop a novel composite insulating material system that, through rational material selection and structural design, ensures excellent insulation performance while also maintaining high heat resistance and good interfacial compatibility to meet increasingly stringent electromagnetic wire insulation requirements. Summary of the Invention

[0007] This application provides a PEEK composite insulated electromagnetic wire containing thermally conductive filler and its preparation method, which solves the problems existing in the prior art.

[0008] This application provides a polyetheretherketone composite insulated electromagnetic wire containing thermally conductive filler, comprising a copper conductor and a first insulating layer, a second insulating layer, and a third insulating layer sequentially disposed on the surface of the copper conductor; the first insulating layer and the third insulating layer are both composite layers of polyetheretherketone and nano-silica hyperbranched polyester; the second insulating layer is a nano-silica hyperbranched polyester layer containing hydroxylated boron nitride nanosheets; the total amount of hydroxylated boron nitride nanosheets added accounts for 2%-4% of the solid content of the nano-silica hyperbranched polyester; the hydroxylated boron nitride nanosheets include hydroxylated boron nitride nanosheets of different sizes, and the hydroxylated boron nitride nanosheets of different sizes are gradient distributed in the thickness direction of the second insulating layer.

[0009] Furthermore, the hydroxylated boron nitride nanosheets with different sheet sizes include large-diameter hydroxylated boron nitride nanosheets, medium-diameter hydroxylated boron nitride nanosheets, and small-diameter hydroxylated boron nitride nanosheets; the large-diameter hydroxylated boron nitride nanosheets have a sheet diameter of 1.5-3 μm and a sheet thickness of 3-5 nm; the medium-diameter hydroxylated boron nitride nanosheets have a sheet diameter of 0.5-1.5 μm and a sheet thickness of 1-3 nm; and the small-diameter hydroxylated boron nitride nanosheets have a sheet diameter of 0.2-0.5 μm and a sheet thickness of 1-2 nm.

[0010] Furthermore, the mass ratio of the large-diameter hydroxylated boron nitride nanosheets, the medium-diameter hydroxylated boron nitride nanosheets, and the small-diameter hydroxylated boron nitride nanosheets is 1:2:2.

[0011] Furthermore, the total amount of the hydroxylated boron nitride nanosheets accounts for 3% of the solid content of the nano-silica hyperbranched polyester.

[0012] Furthermore, the nano-silica hyperbranched polyester is prepared by reacting hyperbranched polyester with nano-silica at a mass ratio of 1.35:1.

[0013] Furthermore, in the first insulating layer and the third insulating layer, the nano-silica hyperbranched polyester and polyether ether ketone are mixed at a mass ratio of 2.35:1.

[0014] Furthermore, the thickness of the first insulating layer is 15 μm, the thickness of the second insulating layer is 22 μm, and the thickness of the third insulating layer is 65 μm.

[0015] Furthermore, the first insulating layer is baked at 390°C for 75 seconds, the second insulating layer is baked at 370°C for 50 seconds, and the third insulating layer is baked at 390°C for 100 seconds.

[0016] A method for preparing a polyetheretherketone (PEEK) composite insulated electromagnetic wire containing thermally conductive filler includes: dispersing hydroxylated boron nitride nanosheets in dimethylformamide, adding nano-silica hyperbranched polyester to obtain a coating solution containing hydroxylated boron nitride nanosheets; mixing the nano-silica hyperbranched polyester with a PEEK varnish to obtain a mixture; coating the mixture onto the surface of a copper conductor and baking to form a first insulating layer; coating the coating solution containing hydroxylated boron nitride nanosheets onto the surface of the first insulating layer and baking to form a second insulating layer; coating the mixture onto the surface of the second insulating layer and baking to form a third insulating layer; wherein the total amount of hydroxylated boron nitride nanosheets added accounts for 2%-4% of the solid content of the nano-silica hyperbranched polyester, and the hydroxylated boron nitride nanosheets include hydroxylated boron nitride nanosheets of different diameters, with the hydroxylated boron nitride nanosheets of different diameters forming a gradient distribution in the thickness direction of the second insulating layer.

[0017] Furthermore, the hydroxylated boron nitride nanosheets with different sizes were prepared by ultrasonic exfoliation for different times; large-size hydroxylated boron nitride nanosheets were ultrasonically exfoliated for 6 h, medium-size hydroxylated boron nitride nanosheets for 12 h, and small-size hydroxylated boron nitride nanosheets for 20 h.

[0018] One or more technical solutions provided in the embodiments of this application have at least the following technical effects or advantages: By introducing hydroxylated boron nitride nanosheets into a hyperbranched polyester system of nano-silica and compounding them with polyetheretherketone (PEEK), a three-layer gradient composite insulation structure is formed. The hydrogen bond network between the boron hydroxyl groups on the surface of the hydroxylated boron nitride nanosheets and the terminal carboxyl or hydroxyl groups of the hyperbranched polyester, as well as the silanol groups on the surface of the nano-silica, can inhibit the agglomeration of nanofillers and improve interfacial compatibility. Through the graded combination of hydroxylated boron nitride nanosheets of different sizes, a self-gradient distribution can be formed in the coating thickness direction by utilizing the difference in sedimentation rate. This allows large-diameter sheets to accumulate in the bottom layer to form a thermally conductive barrier skeleton, while small-diameter sheets accumulate in the upper layer to form an interfacial anchoring layer. This improves the breakdown voltage, insulation resistance, high-temperature resistance, interlaminar shear strength, partial discharge initiation voltage, and corona resistance, and also improves the uniformity of filler dispersion and the stability of the coating structure. Detailed Implementation

[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to limit the invention; the term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0020] Example 1: In this example, hydroxylated boron nitride nanosheets (fBNNSs) are used as interface-modified functional fillers. They are introduced into a nano-silica hyperbranched polyester system and compounded with polyetheretherketone varnish to form a three-layer gradient composite insulation structure. The amount of fBNNSs added is 3% in this example, calculated as the mass ratio of the nano-silica hyperbranched polyester solid content.

[0021] A method for preparing a PEEK composite insulated electromagnetic wire containing thermally conductive filler is as follows: 1 g of hexagonal boron nitride powder was dispersed in 300 g of deionized water and stirred continuously for 30 min. 80 g of sodium hydroxide was added, and stirring continued until completely dissolved. The mixture was placed in an ultrasonic homogenizer and ultrasonically exfoliated at 80 kHz and 300 W for 15 h. After ultrasonic treatment, the dispersion was centrifuged at 3000 rpm for 30 min to remove unexfoliated h-BN. The supernatant was collected, filtered through a 100 nm pore size mixed cellulose membrane, and repeatedly washed with deionized water until the filtrate pH=7. The filter cake was dried in a vacuum oven at 80℃ for 8 h to obtain hydroxylated boron nitride nanosheets. The obtained fBNNSs had a sheet diameter of 0.5–1.5 μm, a sheet thickness of 1.5–3 nm, and a B-OH mass fraction of 5.5%–6.5%.

[0022] 6 g of polylactic acid was added to tetrahydrofuran solvent and stirred until completely dissolved. After dissolution, 3.5 g of succinic anhydride was added, and 0.08 g of stannous octoate catalyst was slowly added dropwise while stirring. The reaction was carried out in a water bath at 95 °C for 5 h. After the reaction was completed, the solvent was removed by vacuum distillation, the product was washed three times with deionized water, filtered, and dried under vacuum at 60 °C for 6 h to obtain carboxylated polylactic acid.

[0023] Solution A was prepared by mixing 90 g of acrylic acid, 12.5 g of vinyltriethoxysilane, 80 g of deionized water, and 3 g of propylene glycol. Solution B was prepared by mixing 4.5 g of mercaptopropionic acid, 0.15 g of vitamin C, 50 g of deionized water, and 3.5 g of propylene glycol. Solution B was slowly added dropwise to solution A under continuous stirring. After the addition was complete, the temperature was raised to 75°C, and the reaction was continued with stirring for 6 h to obtain the acrylic acid-modified silane coupling agent.

[0024] 3.0 g of CBz-2-amino-1,3-propanediol was added to N,N-dimethylformamide solvent and stirred until dissolved. Then, 1.4 g of carboxylated polylactic acid, 1.8 g of acrylic acid-modified silane coupling agent, and 0.05 g of dibutyltin dilaurate were added sequentially. The esterification reaction was carried out at 105 °C for 22 h. After the reaction was completed, the mixture was washed with acetone for 5 h, filtered, and then dried under vacuum at 70 °C for 8 h to obtain hyperbranched polyester.

[0025] The obtained hyperbranched polyester was added to dichloromethane solvent and stirred until completely dissolved. Then, nano-silica was added, with a mass ratio of hyperbranched polyester to nano-silica of 1.35:1. The mixture was stirred at 55°C for 5 h to obtain nano-silica hyperbranched polyester; this was then mixed with polyetheretherketone paint at a mass ratio of 2.35:1 and stirred at room temperature for 30 min until homogeneous to obtain a mixture.

[0026] The fBNNSs obtained in the previous step were dispersed in N,N-dimethylformamide and sonicated at 40 kHz and 200 W for 30 min to form a uniform dispersion. The fBNNSs dispersion was slowly added dropwise to the obtained nano-silica hyperbranched polyester system at a ratio of 3% of the fBNNSs content in the nano-silica hyperbranched polyester, under stirring. After the addition was complete, the reaction was continued at 60 °C for 4 h with stirring, allowing the B-OH groups on the fBNNSs surface to form a hydrogen bond network with the terminal carboxyl / hydroxyl groups of the hyperbranched polyester and the silanol groups on the nano-SiO2 surface. After the reaction, some of the solvent was removed by vacuum distillation to obtain a nano-silica hyperbranched polyester composite dispersion containing fBNNSs. This was diluted with N,N-dimethylformamide to a solid content of 20% and stirred for 30 min to obtain the coating solution.

[0027] The copper conductor is drawn into wires with a diameter of 1.0 mm. After cleaning the conductor surface, three layers of coating are applied sequentially: First insulating layer: A mixture is coated onto the conductor surface, with the coating thickness controlled at 15 μm. After coating, it is baked in an oven at 390℃ for 75 s, and then naturally cooled to room temperature to obtain the first insulating layer.

[0028] Second insulating layer: A coating liquid is applied to the surface of the first insulating layer, with the coating thickness controlled at 22 μm. After coating, it is baked in an oven at 370℃ for 50 s and then naturally cooled to room temperature to obtain the second insulating layer.

[0029] Third insulating layer: A mixture is coated onto the surface of the second insulating layer, with the coating thickness controlled at 65 μm. After coating, it is baked in an oven at 390℃ for 100 s and then naturally cooled to room temperature to obtain the third insulating layer.

[0030] The conductor, after completing the three-layer insulation coating, is wound up and packaged.

[0031] Compared with the control group without fBNNSs, its breakdown voltage is ≥13 kV and insulation resistance is 2×10. 16 Ω, 800℃ mass residue rate of 88.7%~91.7%, interlaminar shear strength as the benchmark value; when the fBNNSs addition amount is 1%, 4.5%, and 8%, the breakdown voltage reaches 14~15 kV, 16~18 kV, and 14~16 kV respectively, and the insulation resistance remains 2×10 at 1% and 4.5%. 16 At Ω and 8%, it slightly decreases to 1×10 16 ~2×10 16 Ω, the mass residue at 800℃ is increased to 90%–92%, 93%–94%, and 91%–93%, respectively, and the interlaminar shear strength is increased by 5%–7%, 18%–23%, and 11%–17%, respectively; when the addition exceeds the upper limit to 12%, due to the aggregation of fBNNSs, the breakdown voltage drops to 10–12 kV, and the insulation resistance drops to 1×10. 15 ~1×10 16 Ω, the mass residue at 800℃ drops to 87%~99%, and the improvement in interlaminar shear strength narrows to 5%~10%, indicating that fBNNSs significantly improves breakdown voltage, insulation resistance, high temperature resistance and interlaminar bonding strength within the preferred range of 2%~4% through hydrogen bond anchoring, crystallization inhibition and deep trap effect. Excessive fBNNSs will lead to defects introduced by agglomeration and reduce the overall performance.

[0032] Example 2: This example uses a graded combination of hydroxylated boron nitride nanosheets (fBNNSs) with different flake sizes as an interface-modified functional filler. Utilizing the difference in sedimentation rates of large, medium, and small fBNNSs in the coating solution, a self-gradient distribution is formed along the coating thickness direction, thereby transforming the grade imbalance into a functional gradient. The total amount of fBNNSs added is 3% in this example, calculated as the mass ratio of the solid content of the hyperbranched polyester nano-silica, where the ratio of large flake size to medium flake size to small flake size is 1:2:2.

[0033] fBNNSs with different sheet sizes were prepared by using different ultrasonic ablation times; Large-diameter fBNNSs were prepared by ultrasonic exfoliation for 6 hours. The flake diameter was 1.5–3 μm, the flake thickness was 3–5 nm, and the B-OH mass fraction was 4%–6%.

[0034] Medium-sized fBNNSs were prepared by ultrasonic exfoliation for 12 hours. The flake diameter was 0.5–1.5 μm, the flake thickness was 1–3 nm, and the B-OH mass fraction was 5%–7%.

[0035] Small-diameter fBNNSs were prepared by ultrasonic exfoliation for 20 hours. The flake diameter was 0.2–0.5 μm, the flake thickness was 1–2 nm, and the B-OH mass fraction was 6%–8%.

[0036] Different fBNNSs gradations with different sheet diameters (large sheet diameter: medium sheet diameter: small sheet diameter = 1:2:2, total addition amount accounts for 3% of the solid content of nano-silica hyperbranched polyester) were used. Comparative Example 1 was a scheme using only medium-diameter fBNNSs with a total addition amount of 3%, and Comparative Example 2 was a scheme without fBNNSs. The results showed that Example 2 had a breakdown voltage ≥20 kV and a DC insulation resistance of 2×10⁻⁶ kV. 16 Comparative Example 1 had a breakdown voltage of only 16 kV, a mass surplus of 94.6% at 800℃, an interlaminar shear strength approximately 28% higher than the control group without fBNNSs, and a partial discharge initiation voltage approximately 15% higher than Example 1; Comparative Example 2 had a breakdown voltage of only 13 kV, an insulation resistance of 2 × 10⁻⁶ kV, and an insulation resistance of 94.6% at 800℃. 16 Ω, 800℃ mass surplus rate of 88.7%, and interlaminar shear strength as the baseline values; compared with Example 1 (breakdown voltage ≥18 kV, 800℃ mass surplus rate of 93.5%, and interlaminar shear strength increased by about 20%), Example 2 utilizes the difference in sedimentation rate to form a self-gradient structure in the coating thickness direction by using a graded combination of fBNNSs with different sheet sizes. Large-diameter sheets are enriched in the bottom layer to form a thermally conductive barrier skeleton, while small-diameter sheets are enriched in the upper layer to form a strong interface anchoring layer. Thus, without adding any new materials, the grade mismatch is transformed into a functional gradient, resulting in better breakdown voltage, high temperature resistance, interlaminar bonding strength, and partial discharge suppression capability than the control scheme with uniform sheet size and no fBNNSs.

[0037] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. For those skilled in the art, the present invention can have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A polyetheretherketone composite insulated electromagnetic wire containing thermally conductive filler, characterized in that, The device includes a copper conductor and a first insulating layer, a second insulating layer, and a third insulating layer sequentially disposed on the surface of the copper conductor. The first insulating layer and the third insulating layer are both composite layers of polyether ether ketone and nano-silica hyperbranched polyester. The second insulating layer is a nano-silica hyperbranched polyester layer containing hydroxylated boron nitride nanosheets. The total amount of hydroxylated boron nitride nanosheets added accounts for 2%-4% of the solid content of the nano-silica hyperbranched polyester. The hydroxylated boron nitride nanosheets include hydroxylated boron nitride nanosheets of different sizes, and the hydroxylated boron nitride nanosheets of different sizes are gradient distributed in the thickness direction of the second insulating layer.

2. The polyetheretherketone composite insulated electromagnetic wire containing thermally conductive filler according to claim 1, characterized in that, The hydroxylated boron nitride nanosheets of different sizes include large-diameter hydroxylated boron nitride nanosheets, medium-diameter hydroxylated boron nitride nanosheets, and small-diameter hydroxylated boron nitride nanosheets; the large-diameter hydroxylated boron nitride nanosheets have a diameter of 1.5-3 μm and a thickness of 3-5 nm; the medium-diameter hydroxylated boron nitride nanosheets have a diameter of 0.5-1.5 μm and a thickness of 1-3 nm; and the small-diameter hydroxylated boron nitride nanosheets have a diameter of 0.2-0.5 μm and a thickness of 1-2 nm.

3. The polyetheretherketone composite insulated electromagnetic wire containing thermally conductive filler according to claim 2, characterized in that, The mass ratio of the large-diameter hydroxylated boron nitride nanosheets, the medium-diameter hydroxylated boron nitride nanosheets, and the small-diameter hydroxylated boron nitride nanosheets is 1:2:

2.

4. The polyetheretherketone composite insulated electromagnetic wire containing thermally conductive filler according to claim 1, characterized in that, The total amount of the hydroxylated boron nitride nanosheets accounts for 3% of the solid content of the nano-silica hyperbranched polyester.

5. The polyetheretherketone composite insulated electromagnetic wire containing thermally conductive filler according to claim 1, characterized in that, The nano-silica hyperbranched polyester is prepared by reacting hyperbranched polyester with nano-silica at a mass ratio of 1.35:

1.

6. The polyetheretherketone composite insulated electromagnetic wire containing thermally conductive filler according to claim 1, characterized in that, In the first insulating layer and the third insulating layer, the nano-silica hyperbranched polyester and polyether ether ketone are mixed at a mass ratio of 2.35:

1.

7. The polyetheretherketone composite insulated electromagnetic wire containing thermally conductive filler according to claim 1, characterized in that, The thickness of the first insulating layer is 15 μm, the thickness of the second insulating layer is 22 μm, and the thickness of the third insulating layer is 65 μm.

8. The polyetheretherketone composite insulated electromagnetic wire containing thermally conductive filler according to claim 1, characterized in that, The first insulating layer is baked at 390°C for 75 seconds, the second insulating layer is baked at 370°C for 50 seconds, and the third insulating layer is baked at 390°C for 100 seconds.

9. A method for preparing a polyetheretherketone composite insulated electromagnetic wire containing thermally conductive filler, characterized in that, include: Hydroxylated boron nitride nanosheets are dispersed in dimethylformamide, and nano-silica hyperbranched polyester is added to obtain a coating solution containing hydroxylated boron nitride nanosheets. The nano-silica hyperbranched polyester is mixed with polyetheretherketone varnish to obtain a mixture. The mixture is coated on the surface of a copper conductor and baked to form a first insulating layer. The coating solution containing hydroxylated boron nitride nanosheets is coated on the surface of the first insulating layer and baked to form a second insulating layer. The mixture is coated on the surface of the second insulating layer and baked to form a third insulating layer. The total amount of hydroxylated boron nitride nanosheets added accounts for 2%-4% of the solid content of the nano-silica hyperbranched polyester. The hydroxylated boron nitride nanosheets include hydroxylated boron nitride nanosheets of different sizes, and the hydroxylated boron nitride nanosheets of different sizes form a gradient distribution in the thickness direction of the second insulating layer.

10. The method for preparing a polyetheretherketone composite insulated electromagnetic wire containing thermally conductive filler according to claim 9, characterized in that, The hydroxylated boron nitride nanosheets with different sizes were prepared by ultrasonic exfoliation for different times; large-size hydroxylated boron nitride nanosheets were ultrasonically exfoliated for 6 h, medium-size hydroxylated boron nitride nanosheets for 12 h, and small-size hydroxylated boron nitride nanosheets for 20 h.